Dodawanie i odejmowanie sum algebraicznych.

1. -(x+6)+(x+7)=
2. -(x-4)-3(2x-5)=
3. -(x+12)-2(x+9)=
4. (2x-7)+2(8x-2)=
5. 3(3x+9)+(x-9)=
6. -(4x-8)+3(x-2)=
7. 2(2x-5)-(x-9)=
8. (3x-2)-2(x-3)=
9. 8(6x-5)-(x+9)=
10. -(4x-1)+(x-6)=
11. (x-6)-3(x-1)=
12. -(12x-3)-(x-6)=
13. 5(4x-1)-2(x+1)=
14. -(6x-2)+3(x+5)=
15. 4(3x+6)-2(3x-8)=
16. -(4x-1)-3(x-5)=
17. 3(2x-5)-8(x+4)=
18. -2(3x+6)+(2x-6)=
19. -8(4x-1)-(x-8)=
20. 2(2x+5)-(x-3)=
21. -5(6x-3+2(x+6)=
22. -3(x+9)-(x+1)=
23. (2x-2)+(x-4)=

prooosze zróbcie mi wszystkie! ;)
przykład; 8(x+12y)-3(x-5y)=8x+96y-3x+15y=5x-81y

3

Odpowiedzi

2010-03-03T20:30:47+01:00
1. -(x+6)+(x+7)=-x-6+x+7=1
2. -(x-4)-3(2x-5)=-x+4-6x+10=-7x+14
3. -(x+12)-2(x+9)=-x-12-2x-18=-3x-30
4. (2x-7)+2(8x-2)=2x-7+16x-4=18x-11
5. 3(3x+9)+(x-9)=9x+27+x-9=10x+18
6. -(4x-8)+3(x-2)=-4x+8+3x-6=-x+2
7. 2(2x-5)-(x-9)=4x-10-x+9=3x-1
8. (3x-2)-2(x-3)=3x-2-2x+6=x+4
9. 8(6x-5)-(x+9)=48x-40-x-9=47x-49
10. -(4x-1)+(x-6)=-4x+1+x+6=-3x+7
11. (x-6)-3(x-1)=x-6-3x+3=-2x-3
12. -(12x-3)-(x-6)=-12x+3-x+6=-13x+9
13. 5(4x-1)-2(x+1)=20x-5-2x+2=18x+3
14. -(6x-2)+3(x+5)=-6x+2+3x+15=-3x+17
15. 4(3x+6)-2(3x-8)=12x+24-6x+16=6x+40
16. -(4x-1)-3(x-5)=-4x+1-3x+15=-7x+16
17. 3(2x-5)-8(x+4)=6x-15-8x-32=-2x-47
18. -2(3x+6)+(2x-6)=-6x-12+2x-6=-4x-18
19. -8(4x-1)-(x-8)=-32x+8-x+8=31x+16
20. 2(2x+5)-(x-3)=4x+10-x+3=3x+13
21. -5(6x-3)+2(x+6)=-30x+15+2x+12=-28x+27
22. -3(x+9)-(x+1)=-3x-27-x-1=-4x-28
23. (2x-2)+(x-4)=2x-2+x-4=3x-6
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-03T20:31:33+01:00
1. -(x+6)+(x+7)=-x-6+x+7=1
2. -(x-4)-3(2x-5)=-x+4-6x+15=-7x+19
3. -(x+12)-2(x+9)=-x-12-2x-18=-3x-30
4. (2x-7)+2(8x-2)=2x-7+16x-4=18x-11
5. 3(3x+9)+(x-9)=9x+27+x-9=10x+18
6. -(4x-8)+3(x-2)=-4x+8+3x-6=-x+2
7. 2(2x-5)-(x-9)=4x-10-x+9=3x-1
8. (3x-2)-2(x-3)=3x-2-2x+6=x+4
9. 8(6x-5)-(x+9)=48x-40-x-9=47x-49
10. -(4x-1)+(x-6)=-4x+1+x-6=-3x-5
11. (x-6)-3(x-1)=x-6-3x+3=-2x-3
12. -(12x-3)-(x-6)=-12x+3-x+6=-13x+9
13. 5(4x-1)-2(x+1)=20x-5-2x-2=18x-7
14. -(6x-2)+3(x+5)=-6x+2+3x+15=-3x+17
15. 4(3x+6)-2(3x-8)=12x+24-6x+16=6x+40
16. -(4x-1)-3(x-5)=-4x+1-3x+15=-7x+16
17. 3(2x-5)-8(x+4)=6x-15-8x-32=-2x-47
18. -2(3x+6)+(2x-6)=-6x-12+2x-6=-4x-18
19. -8(4x-1)-(x-8)=-32x+8-x+8=-33x+16
20. 2(2x+5)-(x-3)=4x+10-x+3=3x+13
21. -5(6x-3+2(x+6)=-30x-15+2x+12=-28x-3
22. -3(x+9)-(x+1)=-3x-27-x-1=-4x-28
23. (2x-2)+(x-4)=2x-2+x-4=3x-6
2010-03-03T20:36:39+01:00
1. -(x+6)+(x+7)=-x-6+x+7=1
2. -(x-4)-3(2x-5)=-x+4-6x+15=-7x+19
3. -(x+12)-2(x+9)=-x-12-2x-18=-3x-30
4. (2x-7)+2(8x-2)=2x-7+16x-4=18x-11
5. 3(3x+9)+(x-9)=9x+9+x-9=10x
6. -(4x-8)+3(x-2)=-4x+8+3x-6=-x+2
7. 2(2x-5)-(x-9)=4x-10-x+9=3x-1
8. (3x-2)-2(x-3)=3x-2- 2x+6=x+4
9. 8(6x-5)-(x+9)=48x-40-x-9=47x-49
10. -(4x-1)+(x-6)=-4x+1+x-6=-3x-5
11. (x-6)-3(x-1)=x-6-3x+1=-2x-5
12. -(12x-3)-(x-6)=-12x+3-x+6=-13x+9
13. 5(4x-1)-2(x+1)=20x-5-2x-2=18x-7
14. -(6x-2)+3(x+5)=-6x+2+3x+15=3x+17
15. 4(3x+6)-2(3x-8)=12x+24-6x+16=6x+40
16. -(4x-1)-3(x-5)=-4x+1-3x+15=-7x+16
17. 3(2x-5)-8(x+4)=6x-15-8x-32=-2x-47
18. -2(3x+6)+(2x-6)=-6x-12+2x-6=-4x-18
19. -8(4x-1)-(x-8)=-32x+8-x+8=33x+16
20. 2(2x+5)-(x-3)=4x+10-x-3=3x+7
21. -5(6x-3+2(x+6)=-30x+15+2x+12
22. -3(x+9)-(x+1)=-3x-27-x-1=-4x-28
23. (2x-2)+(x-4)=2x-2+x-4=3x-6